Pelatihan Pembuatan Media Pembelajaran E-Book Berbasis Heyzine-Canva sebagai Upaya Peningkatan Kompetensi Profesional Guru melalui MGMP - Hartanti Hartanti; Alifiani Alifiani; Anies Fuady (Dinamika Sosial : Jurnal Pengabdian Masyarakat dan Transformasi Kesejahteraan, 2025)
Training on creating Heyzine-Canva-based e-book learning media through the Subject Teacher Working Group (MGMP) aims to improve teachers' professional competence in facing educational demands and digital technology integration. This training activity is designed using demonstration, hands-on practice, and group discussion methods, so that it can accommodate various levels of technology mastery among teachers. Through this training, teachers are guided to develop interactive e-books, learning videos, and innovative digital quizzes using the Heyzine and Canva platforms. The training results show a significant improvement in teachers' skills in utilizing digital media, confidence in integrating technology into learning, and motivation to continue innovating. Additionally, this training also encourages collaboration among teachers and builds a professional network that supports continuous development. Challenges faced, such as variations in technology skills and device limitations, are addressed through ongoing mentoring and further training. This training contributes to improving the quality of learning, student engagement, and supports the achievement of national education goals in the digital era.